1990
DOI: 10.1115/1.2906199
|View full text |Cite
|
Sign up to set email alerts
|

Bond Coat Development for Thermal Barrier Coatings

Abstract: The use of thermal barrier coatings on high-pressure turbine components can improve gas turbine efficiency through reduction of cooling airflow. However, to reduce cooling airflow, a highly reliable thermal barrier coating is required. This increased reliability will be achievable through several complimentary approaches: material and process development, life prediction method development, and engine service experience. The results of bond coat material development, which has increased the thermal cycle life … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

1992
1992
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To perform comparative assessment of oxidation resistance of the studied filler materials CMSX-4 alloy samples with deposited beads were tested for cyclic oxidation in CM FURNACES Bloomfield-1710BL (c) unit in the following mode: heating up to 1150 °C for 5 min + soaking at maximum temperature for 50 min + cooling to 50 °C for 5 min [3]. This mode is used for assessment of thermal-fatigue life of coated samples.…”
mentioning
confidence: 99%
“…To perform comparative assessment of oxidation resistance of the studied filler materials CMSX-4 alloy samples with deposited beads were tested for cyclic oxidation in CM FURNACES Bloomfield-1710BL (c) unit in the following mode: heating up to 1150 °C for 5 min + soaking at maximum temperature for 50 min + cooling to 50 °C for 5 min [3]. This mode is used for assessment of thermal-fatigue life of coated samples.…”
mentioning
confidence: 99%
“…Maintaining the integrity of the bond coat is crucial to ensuring the TBC operates reliably. Of particular importance is the creep performance of the MCrAlY bond coat [2] and it has been shown that creep resistant bond coats improve TBC thermal cycle life [5]. MCrAlY bond coats typically consist of fcc Ni(Co)-γ-phase, bcc B2 NiAl-β-phase, ordered Ni 3 (Al,Ti) γ' phase and CrCo σ phase [3,[6][7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…This behaviour may be due to interfacial oxidation or the formation of brittle interfacial phases [39]. In cases where such a deleterious reaction occurs between coating and substrate (or with an impurity which can diffuse to and react at the interface) a bonding layer can be deposited as a diffusion barrier to improve performance.…”
mentioning
confidence: 98%